SOSIOLOGI MASYARAKAT DITINJAU DARI PERSPEKTIF TUHA PEUT SEBAGAI FUNGSIONARIS GAMPONG DI KECAMATAN MEURAH MULIA - Kamaruzzaman, Kamaruzzaman (Fakultas Ushuluddin Adab dan Dakwah IAIN Lhokseumawe, 2021)
The title of this research is the traditional institution Tuha Peut as a village functionary in Meurah Mulia sub-district, this research is a field study (field research) using qualitative. the results of the study are as follows first, the function of the peut and the way the problem varies greatly according to the problems that exist in the community secondly, the function of Tuha Peut in the Meurah Mulia community is as the heart of the development of the Gampong community, where its existence can provide an inspiration, innovation, and mediation in educating the Gampong community.The progress of the withdrawal of the village greatly influenced the active Tuha Peut institution, Gampong Menasah Manyang, today many social activities have been carried out including.Election of Geuchik Gampong, Determination of people who are entitled to receive zakat and those who are entitled to give zakat, give warnings to guests, especially men who visit late at night at the homes of women who are not Muslim, Geuchik's performance controller, making gampong laws. Third, customary sanctions have not been implemented because Tuha Peut is less able to design customary qanuns to the maximum. Fourth, Tuha Peut has a very large role, in which its role as the Center of Share Idea in all dimensions or programs to be carried forward, both concerning development Irrigation and other social activities.